Antiemetic efficacy of capsicum plaster on acupuncture points in patients undergoing thyroid operation - Min Seok Koo (Korean Journal of Anesthesiology, 2013)
BackgroundPostoperative nausea and vomiting (PONV) occurs in up to 63-84% of patients after thyroid surgery. This study aims to assess the effects of using a capsicum plaster to reduce PONV after thyroid surgery at either the Chinese acupuncture point (acupoint) Pericardium 6 (P6) or Korean hand acupuncture point K-D2.MethodsOne-hundred eighty-four patients who underwent thyroid surgery were randomized in four groups (n = 46 each): control group = inactive tape at P6 acupoints and on both shoulders as a nonacupoint; P6 group = capsicum plaster at P6 points and inactive tape on both shoulders; K-D2 group = capsicum plaster at K-D2 acupoints and inactive tape on both shoulders; Sham group = capsicum plaster on both shoulders and inactive tape at P6 acupoints. The capsicum plaster was applied before the induction of anesthesia and removed at 8 hr after surgery.ResultsThe incidence and severity of nausea and vomiting and the need for rescue antiemetics were decreased in the patients in the P6 and K-D2 groups compared to the patients in the control and sham groups (P < 0.001). The patients in the P6 and K-D2 groups also reported that they were more satisfied (P < 0.05).ConclusionsWe conclude that the capsicum plaster at the P6 and K-D2 acupoint was a promising antiemetic method for the patients undergoing thyroid surgery.